Contrasting distributional patterns of two co-occurring ctenophores in relation to ichthyoplankton and environmental features in the Southwestern Atlantic Ocean - Sobrero, Lucila (2023)
Assessing the ecological role of ctenophores is crucial to understanding ecosystem functioning, including the recruitment of fish stocks. During austral summer in the North Patagonia Ecosystem (NPE) (41-48 ° S), the ctenophores Mnemiopsis leidyi and Pleurobrachia pileus co-occur with the peak of ichthyoplankton abundance of two important fishing resources: the Argentine anchovy Engraulis anchoita and the Argentine hake Merluccius hubbsi, in association with a highly productive tidal front system. 367 plankton samples collected in the NPE over 13 years (2005-2018) were analyzed to determine the abundance and spatial distribution of M. leidyi and P. pileus, their spatial overlap with ichthyoplankton (eggs and larvae of hake and anchovy), and their relation with environmental features. Both ctenophore species displayed contrasting distributional patterns, associated with different physical environments, particularly temperature. Mnemiopsis leidyi showed a higher spatial overlap with ichthyoplankton compared to P. pileus. In addition, there was also a significant negative correlation between the biomass of M. leidyi and the abundance of both fish larvae, suggesting a potential negative impact (via predation and competition) on the survival and recruitment of these two fisheries resources.